E-Channel as an Instrumment for Sharia Financial Inclusion in the Digital Era - Diana Ambarwati; Farra Tia Wardani Farra Tia Wardani (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Meto, 2026)
This research aims to analyze the role of E-Channel as an instrument of Islamic financial inclusion in the digital era. The research method uses a qualitative descriptive approach with literature review from Bank Indonesia, the Financial Services Authority, and various related research results. The results of the study show that E-Channel contributes significantly to increasing Islamic financial literacy and inclusion, especially through easy access to halal financial services for people in remote areas. However, challenges such as low digital literacy, cybersecurity, and infrastructure readiness still need to be a common concern. This study concludes that the development of E-Channels in banking has a significant role in expanding Islamic financial inclusion and strengthening the Islamic financial system in the digital era. Through service innovations such as mobile banking, internet banking, sharia ATMs, and Sharia QRIS, people gain ease of access to various financial products, including savings, microfinancing, and digital zakat. The increase in transaction efficiency and transparency resulting from the use of E-Channels strengthens public trust in Islamic financial institutions and encourages the creation of a safer, faster, and well-documented financial system. Thus, E-Channel not only serves as a financial technology instrument, but also as a manifestation of Islamic ethical values in expanding inclusive and equitable economic access. However, the effectiveness of E-Channel implementation still faces challenges in the form of low digital literacy, data security risks, and infrastructure limitations in rural areas that need to be overcome through cross-agency synergy and community capacity building.